Analisis Determinan Kepatuhan Wajib Pajak Orang Pribadi pada KPP Pratama Balikpapan Timur - De Grave, Anita; Putri, Dhiya Elvira (Visioner : Jurnal Manajemen dan Bisnis, 2025)
This study aims to provide an in-depth understanding of the influence of tax socialization, the quality of fiscas service, the implementation of e-filling, and tax sanctions on the compliance of individual taxpayers. The research sample consisted of 120 individual taxpayers registered at the east Balikpapan tax office (KPP Pratama Balikpapan Timur). Employing a quantitative approach, this study applied multiple linear regresiion analysis to examine the relationships among the variables. The findings of the result that (1) tax socialization has positive and significant effect on individual taxpayer compliance, (2) the quality of fiscal service show no significant enfluence on taspayer compliance behavior of individual taxpayers. The study involved 120 respondents registered at the East Balikpapan Tax Office (KPP Pratama Balikpapan Timur) as the research sample. Using a quantitative research design, the analysis was conducted through the application of multiple linear regression techniques to test the influence of each independent variable both individually and jointly. The empirical results indicate that tax dissemination significantly and positively contributes to individual taxpayer compliance, whereas the quality of fiscal services shows no significant positive relationship. The adoption of e-filing systems demonstrates a significant positive impact on compliance, while tax penalties appear to exert no substantial effect. Furthermore, when analyzed collectively, all four variables—tax dissemination, fiscal service quality, e-filing implementation, and tax sanctions—exhibit a significant combined influence on compliance behavior. Overall, the findings underscore that enhancing tax education and optimizing digital tax systems play a critical role in strengthening voluntary compliance, while service quality and sanction enforcement alone may not effectively shape compliant behavior among individual taxpayers